Improving the Quality of “Leri” Rice Washing Waste by Different Period of Fermentation and Yeast Concentration as an Alternative Liquid Organic Fertilizer - Muh. Akhsan Akib; Henny Setiawaty; Haniarti Haniarti; Sulfiah Sulfiah (Hasanuddin University, 2014)
This study aims to determine the best time of fermentation process and yeast concentration to improve the quality of “leri” (rice wahing waste). The study was conducted in the Bilibili village, Suppa Sub-District, Pinrang Regency, South Sulawesi Province from April to July 2012. Samples were analyzed at the Laboratory of Chemical and Food Livestock, Hasanuddin University, and Laboratory of Chemistry Department of Mines and Energy, Makassar. The study used a Completely Randomized Design (CRD) factorial pattern. The first factor i.e., treatment of fermentation period consist of a control, 2, 4, and 6 of fermentation period. The second treatment is the mass of yeast consisting of a control 1, 2, and 3 g of yeast per 5 liters of leri. Data were analyzed by two factor analysis of variance without replication. Duncan test was used for significant treatment. The result shows that the time of fermentation for 6 days produce relatively high ethanol (0,52 %), increasing the mineral content of phosphorus (0,15 ppm) and sulfur (0,35 %), and mineral content of nitrogen are relatively good (0,11 %). Yeast 3g per 5 liters of leri, gave betterethanol result (0,43 %), increased mineral content of nitrogen (0,11 %) and phosphorus (0,16 ppm), and potassium mineral content were quite good (350,25 ppm).